(untitled) (Research, Society and Development, 2024)
Introduction: The transgender person does not identify with the biological sex designated at birth. This lack of identification ends up causing anxious, depressive episodes and suicidal ideations. In this context, hormone transition therapy makes it possible to obtain characteristics of the desired gender. Objectives: To understand the impacts of hormonal therapies on the mental health of trans young people, elucidating whether there is a post-transition benefit in this scenario. Methodology: This review considered 14 articles found in PUBMED and 6 found in Google Scholar from the descriptors (transgender); (hormonal therapy) and (mental health). Studies dating back more than 5 years; incomplete texts; languages other than English or Portuguese and articles that did not concomitantly contemplate mental health and transgender were excluded. Discussion/Results: The study population was transgender women and men between 9 and 25 years old. The analysis time was from 3 months to 5 years. Among the articles, 12 agreed that access to hormone therapy is associated with improvements in quality of life and reduction in depression rates and an article suggests that there was no clinically significant change in mood symptoms, given the limitation of the population in study. Some articles portrayed the need to expand access to hormone therapy. Conclusion: Hormone therapy was associated with better quality of life and decreased depression and anxiety symptoms, probably due to identification with acquired physical characteristics. However, it is necessary to track diseases before, during and after the hormonal transition.